Corrosion Inhibition Property of Some 1, 3, 4- Thiadiazolines on Mild Steel in Acidic Medium - A. Shamitha Begum; J. Mallika; P. Gayathri (E-Journal of Chemistry)
The present work deals with the corrosion behavior of mild steel in acidic medium. The inhibitive effect of substituted 1, 3, 4-Thiadiazol-2-amines on the corrosion of mild steel in 1 M H2SO4 has been studied by weight loss and electrochemical methods. The electrochemical parameters for mild steel in acidic solution with and without inhibitor were calculated. The effect of temperature on the corrosion rate, activation energy and free energy of adsorption were also calculated. The synergistic effect has been studied by weight loss and electrochemical methods. The electrochemical parameters for mild steel in acidic solution were also calculated.